2015
DOI: 10.3390/ma8125440
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biocompatible Hydroxyapatite Using Chitosan Oligosaccharide as a Template

Abstract: In this study, a novel biocompatible hydroxyapatite (HA) was synthesized by using chitosan oligosaccharide (COS) as a template. These HA samples were studied by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM). The biocompatibility of HA samples was evaluated via cell viability, cell morphology and alkaline phosphatase staining of MG-63 cell lines. The results show that HA synthesized in the presence of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The diffraction peaks appeared in these synthesized HA agree with those of the standard HA (JCPDS No. 09-0432) [7,8], which indicated that the HA crystals have been successfully synthesized. According to the Figure 1, peaks observed at 2θ degree of 26.1, 32.1, 33.0, 40.1, 47.0, 49.7 and 53.4 can be recognized to (002), (211), (300), (310), (222), (213) and (004) reflections of HA [26,27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffraction peaks appeared in these synthesized HA agree with those of the standard HA (JCPDS No. 09-0432) [7,8], which indicated that the HA crystals have been successfully synthesized. According to the Figure 1, peaks observed at 2θ degree of 26.1, 32.1, 33.0, 40.1, 47.0, 49.7 and 53.4 can be recognized to (002), (211), (300), (310), (222), (213) and (004) reflections of HA [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we found the size of HA can be affected by the molecular weight of chitosan oligosaccharide [8]. However, the morphology and size are difficult to control under ~100 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional calcium ions could react with phosphate ions and produce water-insoluble hydroxyl-appetite salts on the surface (Figures 2, 4 and 6). 41 Moreover, Wang et al 42 showed that the amino groups on the surface of chitosan have the ability to chelate Ca 2+ ions to form ionic clusters for the nucleation of minerals and function like a natural template for the apatite crystal to grow. This resulted in formation of calcium silicate, which was observable in XRD spectra.…”
Section: Mechanisms Of Bioactivitymentioning
confidence: 99%
“…Afterwards, this phase transforms into bone-like apatite crystals, increasing its Ca: P ratio. 41 Moreover, Wang et al 42 showed that the amino groups on the surface of chitosan have the ability to chelate Ca 2+ ions to form ionic clusters for the nucleation of minerals and function like a natural template for the apatite crystal to grow. The SEM micrographs in our study (Figures 2, 4 and 6) showed hydroxyl-appetite depositions on the surface, forming a roughly irregular surface after a day of immersion.…”
Section: Mechanisms Of Bioactivitymentioning
confidence: 99%